2022
DOI: 10.1002/pon.6037
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and acceptability of written exposure therapy in addressing posttraumatic stress disorder in Iranian patients with breast cancer

Abstract: Objective This study examined the feasibility and acceptability of written exposure therapy (WET) in reducing symptoms of posttraumatic stress disorder (PTSD) in Iranian women with breast cancer. Secondary aims included examining the influence of WET on quality of life (QoL), overgeneral memory and illness perceptions. Method Forty‐six females with breast cancer and clinical symptoms of PTSD referred to the Razi Hospital in Rasht, Iran were randomly assigned to either WET (n = 23) or control (n = 23) groups. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
(108 reference statements)
0
10
0
Order By: Relevance
“…Table 1 displays information regarding each of the 17 articles included in the review. Notably, 14 (82%) articles were published since 2020 (Ahmadi et al, 2022; Andrews et al, 2022; Ellis et al, 2023; LoSavio et al, 2023; Morissette et al, 2023; Nillni et al, 2023; Park et al, 2021; Schacht et al, 2023; Schumacher et al, 2023; Sloan et al, 2022, 2023; Tyler et al, 2022; Yun & Lee, 2022; Zolfa et al, 2023). Study sample sizes ranged from three to 277.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 displays information regarding each of the 17 articles included in the review. Notably, 14 (82%) articles were published since 2020 (Ahmadi et al, 2022; Andrews et al, 2022; Ellis et al, 2023; LoSavio et al, 2023; Morissette et al, 2023; Nillni et al, 2023; Park et al, 2021; Schacht et al, 2023; Schumacher et al, 2023; Sloan et al, 2022, 2023; Tyler et al, 2022; Yun & Lee, 2022; Zolfa et al, 2023). Study sample sizes ranged from three to 277.…”
Section: Resultsmentioning
confidence: 99%
“…Study sample sizes ranged from three to 277. Seven (43%) of the studies used an RCT design, with four of these studies comparing WET with a more time-intensive trauma-focused treatment for PTSD (Ahmadi et al, 2022; Sloan et al, 2018, 2022, 2023); one RCT compared WET to a trauma-focused expressive writing condition (Ellis et al, 2023), and the other two RCTs compared WET with a no treatment condition (Sloan et al, 2012; Zolfa et al, 2023). One of the ten open trial studies was a large ( N = 277) hybrid implementation-effectiveness study conducted within the Department of Veterans Affairs (LoSavio et al, 2023); LoSavio et al is one of only three (Morrissette et al, 2023; Sloan et al, 2023) effectiveness studies conducted to date, with the remaining studies representing efficacy design.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Psychosocial research included in this Special Issue identifies individual resiliency factors, such as self‐compassion, in patients with cancer in Xi’An, China 19 and pilot studies are reported demonstrating the feasibility of written exposure therapy for posttraumatic stress disorder in Iranian women with breast cancer 20 and of acceptance and commitment therapy for parents of children with a haematological malignancy or a solid tumour. 21 Asuzu et al 22 report a pilot psychosocial intervention group in Nigeria that shows potential in supporting breast cancer patients.…”
Section: Overview Of the Special Issue Contentmentioning
confidence: 99%